2012
DOI: 10.1177/0748233712448117
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and tissue pathology caused by subacute exposure to ammonium acetate in rats and their response to treatments with alpha-ketoglutarate and N-acetyl cysteine

Abstract: Ammonia is a widely used industrial chemical that is recognized as a potent neurotoxin and environmental pollutant. The present study addresses the oxidative stress and tissue pathology caused by 4 weeks of exposure to ammonium acetate (AMA; 100 mg/kg daily; orally) in rats, and their response to oral treatments with alpha-ketoglutarate (A-KG; 1.0 g/kg), a potential cyanide antidote, and/or N-acetyl cysteine (NAC; 10 mg/kg), an antioxidant. The organ-body weight index of brain and liver was significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…In fact, oxidative stress can also cause renal ammoniagenesis which may contribute to progression of renal injury (Dan et al, 2008). By contrast, a very recent study by Satpute et al observed that subacute exposure to ammonium acetate in rats induces renal necrosis and tubular degeneration, which were not correlated with either oxidative or biochemical changes (Satpute et al, 2014). Indeed, it is apparent that exposure of neutrophils to ammonia impair phagocytosis and promotes increased reactive oxygen species generation that results in oxidative stress at infection sites and collateral damage to host tissue (Shawcross et al, 2008).…”
Section: The Effect Of Ammonia On Other Organs Kidneymentioning
confidence: 97%
“…In fact, oxidative stress can also cause renal ammoniagenesis which may contribute to progression of renal injury (Dan et al, 2008). By contrast, a very recent study by Satpute et al observed that subacute exposure to ammonium acetate in rats induces renal necrosis and tubular degeneration, which were not correlated with either oxidative or biochemical changes (Satpute et al, 2014). Indeed, it is apparent that exposure of neutrophils to ammonia impair phagocytosis and promotes increased reactive oxygen species generation that results in oxidative stress at infection sites and collateral damage to host tissue (Shawcross et al, 2008).…”
Section: The Effect Of Ammonia On Other Organs Kidneymentioning
confidence: 97%
“…On the other hand, a significant decrease was observed in the brain mitochondria during ALF in rats [ 15 ]. Depending on the HA or ALF model employed, the brain activity of the key GSH-metabolizing enzyme, glutathione peroxidase (GPx) was noted to either go up [ 16 ] or down [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the LPS-challenged piglets, AKG supplementation at 1% elevated GSH-Px activity and tended to reduce MDA content in the liver (Wang et al 2015). In a rat model of ammonium poisoning, AKG showed antioxidant properties for the protection of the liver (Satpute et al 2014). In a rat model of ammonium poisoning, AKG showed antioxidant properties for the protection of the liver (Satpute et al 2014).…”
Section: Discussionmentioning
confidence: 92%
“…As an antidote for cyanogen, post-treatment with AKG abrogated cyanogen-induced oxidative damage in the plasma, brain, liver and kidney of rats (Bhattacharya et al 2014). In a rat model of ammonium poisoning, AKG showed antioxidant properties for the protection of the liver (Satpute et al 2014). It has been reported that AKG could detoxify excess ammonia, participate in non-enzymatic oxidative decarboxylation during hydrogen peroxide decomposition, and enhance the proper metabolism of fats, resulting in reduced generation of oxygen radicals and diminished lipid peroxidative damages (Velvizhi et al 2002).…”
Section: Discussionmentioning
confidence: 98%